1983
DOI: 10.1021/bi00289a037
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human plasma kallikrein and its light chain with C.hivin.1 inhibitor

Abstract: The light chain of human plasma kallikrein contains the enzymatic active site. The inactivation of kallikrein and of its isolated light chain by C1 inhibitor was investigated to assess the functional contributions of the heavy-chain region of kallikrein and of high molecular weight kininogen to this reaction. The second-order rate constants for the inactivation of kallikrein or its light chain were respectively 2.7 X 10(6) and 4.0 X 10(6) M -1 min -1. High molecular weight kininogen did not influence the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 42 publications
5
33
0
Order By: Relevance
“…Second, about one-third of native Cl-Inh in plasma is cleaved in vitro to iCl-Inh upon activation of the contact system by kaolin (53) and DXS (45). Third, analytic gel (SDS-PAGE) studies concerning the interaction of Cl-Inh with either kallikrein, Factor XIa, or plasmin have demonstrated the formation of stable high-molecular weight complexes and the appearance of iCl-Inh species (22,(27)(28)(29)56).…”
Section: Ci-cl-inh and Kallikrein-cl-inh Complexes In Patients Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, about one-third of native Cl-Inh in plasma is cleaved in vitro to iCl-Inh upon activation of the contact system by kaolin (53) and DXS (45). Third, analytic gel (SDS-PAGE) studies concerning the interaction of Cl-Inh with either kallikrein, Factor XIa, or plasmin have demonstrated the formation of stable high-molecular weight complexes and the appearance of iCl-Inh species (22,(27)(28)(29)56).…”
Section: Ci-cl-inh and Kallikrein-cl-inh Complexes In Patients Withmentioning
confidence: 99%
“…Several studies have shown that the formation of high-molecular weight target proteinase-C1-Inh complexes is accompanied by the generation of modified (cleaved), inactive Cl-Inh (iCl-Inh) species with a lower apparent molecular weight than native Cl-Inh (23,24,(27)(28)(29). In addition, a number ofendogenous (e.g., neutrophil elastase) and bacterial nontarget proteinases (i.e., proteinases that are not inhibited by Cl-Inh) generate iCl-Inh species by catalytical cleavage ofthe inhibitor in its reactive center (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Chemicals used in the purification of factor XI1 and kallikrein were obtained from sources described previously [16,171. Ovalbumin, diisopropylphosphofluoridate and soybean trypsin inhibitor (SBTI) were from Sigma Chemicals (St Louis, MO).…”
Section: Ma Trr Iulsmentioning
confidence: 99%
“…Factor XI1 preparations were homogeneous and pure as determined by polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate. Human plasma kallikrein and its heavy and light chain were purified as described previously [16]. Two-chain high-M, kininogen was purified according the procedure of Kerbiriou and Griffin [18].…”
Section: Proteinsmentioning
confidence: 99%
See 1 more Smart Citation